2022
DOI: 10.3390/nano12071145
|View full text |Cite
|
Sign up to set email alerts
|

Polydopamine-Coated Magnetic Iron Oxide Nanoparticles: From Design to Applications

Abstract: Magnetic iron oxide nanoparticles have been extensively investigated due to their applications in various fields such as biomedicine, sensing, and environmental remediation. However, they need to be coated with a suitable material in order to make them biocompatible and to add new functionalities on their surface. This review is intended to give a comprehensive overview of recent advantages and applications of iron oxide nanoparticles coated by polydopamine film. The synthesis method of magnetic nanoparticles,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 113 publications
(130 reference statements)
1
23
0
Order By: Relevance
“…Bare Co 3 O 4 NPs had spherical shape with 20.03 ± 2.82 nm diameter, calculated from their TEM images, and importantly, relatively thick (~15 nm) shells were clearly observed outside the core NPs from the PDA@Co 3 O 4 NPs ( Figure 2 a,b). In basic conditions, DA is known to easily interact with the surface of the NPs by a variety of interactions, including electrostatic interaction, metal coordination, and hydrogen bonding, and induce its polymerization among another DA monomers [ 25 , 26 , 27 , 28 , 29 , 30 ]. Thus, it was believed that the layer around the Co 3 O 4 NPs was PDA shell, as also clearly observed in the SEM images ( Figure S1 in Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
“…Bare Co 3 O 4 NPs had spherical shape with 20.03 ± 2.82 nm diameter, calculated from their TEM images, and importantly, relatively thick (~15 nm) shells were clearly observed outside the core NPs from the PDA@Co 3 O 4 NPs ( Figure 2 a,b). In basic conditions, DA is known to easily interact with the surface of the NPs by a variety of interactions, including electrostatic interaction, metal coordination, and hydrogen bonding, and induce its polymerization among another DA monomers [ 25 , 26 , 27 , 28 , 29 , 30 ]. Thus, it was believed that the layer around the Co 3 O 4 NPs was PDA shell, as also clearly observed in the SEM images ( Figure S1 in Supplementary Materials ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PDA coated materials can further react with functional molecules containing amino, sulfhydryl or carboxyl groups through Michael addition and/or Schiff base reaction to realize the advanced applications [ [120] , [121] , [122] , [123] ]. Although the adhesion mechanism between PDA coating and surface have been not uncovered thoroughly, it is demonstrated that the catechol-metal coordination, electrostatic interactions, π-π interactions, hydrogen bonds play an important role [ [124] , [125] , [126] , [127] ]. The manufacture and widespread application of PDA-based materials is developing rapidly, and a number of cost-effective PDA materials have been developed that are expected to be used in energy, biomedicine, water treatment, sensing, surface engineering, and other fields.…”
Section: Polyphenol Based Coating For Particle Surface Engineering An...mentioning
confidence: 99%
“… 3 These features make it very interesting to study the possibility of using melanin as an active material for technological applications, such as molecular electronics and photovoltaic devices, since it is considered as an organic semiconductor. 4 In recent years, the synthetic melanin denominated as polydopamine (PDA) has taken much attention in the field of biomedicine, 5 electronics, 6 bioelectronics, 7 environmental remediation, 8 and photocatalysis. 9 PDA is a material that has a similar chemical structure to eumelanin and easily synthesized.…”
Section: Introductionmentioning
confidence: 99%